2010
DOI: 10.1021/pr901032r
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Provides Insights on Venom Processing in Conus textile

Abstract: Conus species of marine snails deliver a potent collection of toxins from the venom duct via a long proboscis attached to a harpoon tooth. Conotoxins are known to possess powerful neurological effects and some have been developed for therapeutic uses. Using mass-spectrometry based proteomics, qualitative and quantitative differences in conotoxin components were found in the proximal, central and distal sections of the C. textile venom duct suggesting specialization of duct sections for biosynthesis of particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 61 publications
2
65
1
Order By: Relevance
“…Currently only about 130 mature conotoxins (meaning exact termini and modifications) are known after 40 years of study [23], so 15 novel conotoxins represents a substantial contribution to the field. (We have also observed about 35 mature conotoxins that match database sequences in C. textile, slightly exceeding the original analysis of the same data sets [36,37].) Most studies add only one or two de novo sequences at a time.…”
Section: Introductioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Currently only about 130 mature conotoxins (meaning exact termini and modifications) are known after 40 years of study [23], so 15 novel conotoxins represents a substantial contribution to the field. (We have also observed about 35 mature conotoxins that match database sequences in C. textile, slightly exceeding the original analysis of the same data sets [36,37].) Most studies add only one or two de novo sequences at a time.…”
Section: Introductioncontrasting
confidence: 55%
“…We did not obtain Rockefeller's charge-enhanced precursor data [37], only the standard carbamidomethylated cysteine. Sample preparations and data acquisition strategies were as described previously [37,36]. The Scripps data [36] were HCD and CID Orbitrap MS/MS spectra with high-accuracy precursor and fragment masses.…”
Section: Application To Conotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, manual examination revealed that the two most intense ions were either not assigned or incorrectly assigned on the second isotopic peak. By manually analyzing the spectrum with pLabel, we found that an L28V point mutation gave a beautiful fragment ion series from b 27 ϩϩϩϩ to b 23 ϩϩϩϩ, and a T11S point mutation further led to the assignment of b12ϩϩ, b15ϩϩ, b17ϩϩ, b18ϩϩ, b19ϩϩ, and b20ϩϩϩ ions, as well as y11ϩ and y12ϩϩ ions. To match the precursor ion mass, Gly23 was mutated to Thr, which was supported by the b22ϩϩϩ ion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MS-based proteomics techniques have come into favor for the large-scale study of conotoxin sequences. For instance, proteomic analysis of different sections of the Conus textile venom duct has been performed to explore the venom processing (23). Some elegant de novo sequencing works have also been done with conotoxins, but specialized MS methodologies were required (24,25).…”
mentioning
confidence: 99%